Schaum's outline of theory and problems of macroeconomics - Diulio, Eugene A. (Singapore McGraw-Hill Book, 1998)
A concise and practical guide that supplements macroeconomics courses. Includes step-by-step solutions to over 267 problems and 240 additional exercises to support self-study and exam preparation.
Includes index
Keywords: Quản trị kinh doanh